Państwo i jego władca w teorii racji stanu Giovanniego Botero - Wielomski, Adam (Dialogi Polityczne, 2021)
Italian Jesuit Giovanni Botero (1544–1617) is seen as an intellectual father of modern idea of reason of State, and of the State as abstract and unpersonal being. The aim of this text is the complete revision of this popular view. The difference between unpersonal State and personal ruler is in his famous book La Ragion di stato (1589) posed only as theoretical question, because the intellectual fathers of Botero present traditional statement that the prince is the owner of state (Machiavelli) or the power has the origins in the power of father of family (Bodin). From the mixture of state and ruler, reason of State and reason of ruler is possible the identification of state and ruler as one being only. And it is the cause that in Botero we have only one possible political regime: royal monarchy. The people has not the right to revolt, to any form of resistance, and to change the regime of State. Botero is not the modern thinker as he is presented in the literature. He is the mixture between modern and traditional points of view.